2006
DOI: 10.1350/ijps.2006.8.3.218
|View full text |Cite
|
Sign up to set email alerts
|

The New York City Police Department's Compstat: Dream or Nightmare?

Abstract: The Compstat paradigm has revolutionised the way policing is accomplished in democratic countries. Many agencies throughout the world have emulated the Compstat programme which originated in New York City in 1994. The strengths of Compstat have been widely publicised: dramatic reductions in crime, accountability of key staff members, and coordination of various units within an agency.The weaknesses of Compstat are less recognised: due process considerations, community relations, leadership issues, inadequate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…This statistics‐driven managerial system called “Compstat” was created to shake up an ineffectual bureaucracy that was not fighting crime (Eterno and Silverman ). In the early years, commanders feared embarrassment, loss of promotion, and many were removed from commands (Eterno and Silverman ; Silverman ). Bratton left in 1996, but Compstat remained and became a “legalistic‐style numbers game” driven by fear at the highest levels (Eterno and Silverman :223; Eterno and Silverman ).…”
Section: Compstat and Institutional Racismmentioning
confidence: 99%
See 2 more Smart Citations
“…This statistics‐driven managerial system called “Compstat” was created to shake up an ineffectual bureaucracy that was not fighting crime (Eterno and Silverman ). In the early years, commanders feared embarrassment, loss of promotion, and many were removed from commands (Eterno and Silverman ; Silverman ). Bratton left in 1996, but Compstat remained and became a “legalistic‐style numbers game” driven by fear at the highest levels (Eterno and Silverman :223; Eterno and Silverman ).…”
Section: Compstat and Institutional Racismmentioning
confidence: 99%
“…In the early years, commanders feared embarrassment, loss of promotion, and many were removed from commands (Eterno and Silverman ; Silverman ). Bratton left in 1996, but Compstat remained and became a “legalistic‐style numbers game” driven by fear at the highest levels (Eterno and Silverman :223; Eterno and Silverman ).…”
Section: Compstat and Institutional Racismmentioning
confidence: 99%
See 1 more Smart Citation
“…is recorded on a daily basis by all police officers, the numbers are checked by supervisors, and then entered into computerized systems, where they are entered into the Geographic Information Systems used to generate maps. Eterno and Silverman (2006) reported that COMPSTAT was embraced by police executives but actually alienated lower-level officers because of its intensive top-down management style.…”
Section: The Development Of Qol Policing In Nycmentioning
confidence: 99%
“…Case studies and survey research ventures (Weisburd, Mastrofski, McNaley, Greenspan, & Willis, 2003) provide descriptive information about the department-level design and implementation of the Compstat model outside of the NYPD. Commentary by various scholars (Eterno & Silverman, 2006;Firman, 2003;Kania, 2004;Klinger, 2003;Magers, 2004;McDonald, 2000;Moore, 2003;Moore & Braga, 2003;Silverman, 2006;Vito, Walsh, & Kunselman, 2005;Walsh, 2001;Walsh & Vito, 2004;Weisburd, Mastrofski, Willis, & Greenspan, 2006) provides ample food for thought regarding the positive and negative outcomes that the Compstat model has had on police administration. Yet another set of scholars (Braga, 2001;Chilvers & Weatherburn, 2004;Conklin, 2003;Eck & Maguire, 2000;Greene, 1999;Joanes, 1999;Kelling & Bratton, 1998;Kelling & Sousa, 2001;Levitt, 1997Levitt, , 2004Mazerolle, Rombouts, & McBroom, 2007;Rosenfeld, Fornango, & Baumer, 2005;Sousa, 2003;Unter, 2007;Weisberg, 2005) have sought to document the impact that the Compstat model has had on jurisdictional crime rates and various forms of targeted social disorder.…”
Section: Scholarly Research On the Compstat Modelmentioning
confidence: 99%